Predicting trait‐environment relationships for venation networks along an Andes‐Amazon elevation gradient - Benjamin Blonder; Norma Salinas; Lisa Patrick Bentley; Alexander Shenkin; Percy O. Chambi Porroa; Yolvi Valdez Tejeira; Cyrille Violle; Nikolaos M. Fyllas; Gregory R. Goldsmith; Roberta E. Martin; Gregory P. Asner; Sandra Díaz; et al. (Ecology, 2017)
Understanding functional trait‐environment relationships ( TER s) may improve predictions of community assembly. However, many empirical TER s have been weak or lacking conceptual foundation. TER s based on leaf venation networks may better link individuals and communities via hydraulic constraints. We report measurements of vein density, vein radius, and leaf thickness for more than 100 dominant species occurring in ten forest communities spanning a 3,300 m Andes‐Amazon elevation gradient in Peru. We use these data to measure the strength of TER s at community scale and to determine whether observed TER s are similar to those predicted by physiological theory. We found strong support for TER s between all traits and temperature, as well weaker support for a predicted TER between maximum abundance‐weighted leaf transpiration rate and maximum potential evapotranspiration. These results provide one approach for developing a more mechanistic trait‐based community assembly theory.